TINGKAT PENGETAHUAN DAN SIKAP REMAJA PUTRI TENTANG KEHAMILAN USIA DINI DI KOTA DENPASAR - dewa ayu dian krisna dewi; Dinar Lubis (ARCHIVE OF COMMUNITY HEALTH, 2012)
Adolescence pregnancy is a pregnancy among teenage aged between 15-19 years, whichcommonly occur due to increase of sexsual behaviour before marriage among teenage whichmay cause unwanted and unintended preganacy. Adolescence pregnancy have a serious impacton health and psychosocial of the adolescents herself and the o? spring.The aim of this study is to know the level of knowledge, a! itude and behavior of Adolescentgirls in Denpasar towards adolescence pregnancy. The information is important to understandthe risk behavior of teenage girls towards adolescence pregnancy. This study was a descriptivestudy, using cross sectional method, with samples of 284 teenage girls grade 3 in one privateintermediate school in Denpasar. Data was collected by self administered questioner. The results showed that the majority of respondents have high knowledge level (98.6%; n = 280) and moderate knowledge level (1.4%; n = 4) towards adolescent pregnancy. Proportion of gooda! itude was 77.8% (n = 221), moderate a! itude is 21.5% (n = 61) and poor was 0.7% (n 2). Theresult indicate there is a gap beween percentage of students who has a good knowledge (98.6%)with students who has good a! itude level with 98,6% compared to 77,8%. This study showed that the knowledge as predisposing factor of a! itute was not always signi? cantlyrelated with a! itude. Therefore, it is suggested that the school needs to provide counselingprogram, peer education program and IEC (Information, Education and Communication) toincrease skill of the Adolescent girls to prevent adolescent pregnancy.